The Ability to Write Description Text By First Year Students of English Department at Universitas Muhammadiyah Sorong - Ohoira, Muzna (JULIET: Journal of English Language and Literature, 2025)
Writing is a communication activity to convey messages (information) in writing to other parties using written language as a medium. Writing is also very important for students to be able to develop students' critical thinking power towards an issue that is being hotly discussed and expressed in writing activities. This study aims to disclose first year English students’ ability to write descript text at Universitas Muhammadiyah Sorong. This study was held under descriptive qualitative. The participants of this research were the English students of Universitas Muhammadiyah Sorong, in academic year 2023/2024. The researcher used a subjective test as the instrument to obtained the data. the data was collected by giving a subjective test. It is used to describe student’s ability in making descriptive text. the research results it was found that the researcher shows the data that has been added up and provided by the assessor. It can explained that there were 8 (40%) students who got the fairly good category, 6 (30%) got the poor category, 3 students (15%) got the excellent category and 3 students (15%) have a good category. The total score of students' descriptive text writing ability in raters was 1,284 while the test average of the raters was 64.2. That was it It is clear that students' writing ability in descriptive text is included in the fairly good category.